2019
DOI: 10.1007/s10151-019-01936-9
|View full text |Cite
|
Sign up to set email alerts
|

A validated severity score for haemorrhoids as an essential prerequisite for future haemorrhoid trials

Abstract: Background There is a lack of standardised outcomes for haemorrhoidal disease making comparison between trials difficult. A need for a very well validated severity score is essential to facilitate meta-analysis of comparative studies, enabling evidence-based clinical practice. Methods The Hubble trial provides a large cohort of patients with haemorrhoidal disease randomised to rubber band ligation (RBL) or haemorrhoidal artery ligation. The haemorrhoid severity score (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 17 publications
0
33
0
2
Order By: Relevance
“…This utilised the COS-MIN methodology and produced adequate results for the criteria for good measurement properties. The two studies from Lee et al [18] and Rørvik et al [21] showed the HSS to have satisfactory responsiveness, suggesting that it is suitable for use in clinical trials. The HSS was used in two major trials, the HuBBle trial and the eTHoS trial ('Comparison of stapled haemorrhoidopexy with traditional excisional surgery for haemorrhoidal disease') [19,23].…”
Section: Discussionmentioning
confidence: 99%
“…This utilised the COS-MIN methodology and produced adequate results for the criteria for good measurement properties. The two studies from Lee et al [18] and Rørvik et al [21] showed the HSS to have satisfactory responsiveness, suggesting that it is suitable for use in clinical trials. The HSS was used in two major trials, the HuBBle trial and the eTHoS trial ('Comparison of stapled haemorrhoidopexy with traditional excisional surgery for haemorrhoidal disease') [19,23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been successfully validated and considered as an essential tool for future hemorrhoid trials [22].…”
Section: Methodsmentioning
confidence: 99%
“…Face-to-face and telephone interviews were conducted pre- and postoperatively by the direct care team to collect data on patient demographics; diagnostics; postoperative pain and satisfaction scores; and procedure-related complications. We also gave patients a questionnaire to assess their Haemorrhoid Severity Score (HSS), including pain, itching, discomfort, bleeding, soiling, and haemorrhoidal tissue prolapse [9, 10] (Table 1); anal incontinence and quality of life 2–3 weeks before and 6–8 weeks after the procedure. Cleveland Incontinence Score (CIS), European Quality-of-Life Five Dimension, Five Level (EQ-5D-5L), and Visual Analogue Scale (VAS) scores were assessed before and 2 months after the procedure.…”
Section: Methodsmentioning
confidence: 99%